PENDAMPINGAN PERAN DAN POTENSI KEAGAMAAN, SOSIAL DAN EKONOMI DI DUSUN KARANGSEMI KECAMATAN GONDANG KABUPATEN NGANJUK - Arofik, Slamet; Fitri, Abdul Basith Misbahul; Nadhif, Muchammad; Huda, Afiful (LPM STAI Darussalam Krempyang Nganjuk, 2018)
Karangsemi village Gondang Subdistrict is one of the villages in Nganjuk Regency which has the potential to become one of the developing and developed villages. One factor that causes this is ownership of existing human resources. However, because the SDA is not optimal it causes the village to be unable to become a village that has a